Early Radiographic Changes in the Lateral Talocalcaneal Angle Following Achilles Tenotomy in Children With Idiopathic Clubfoot. (March 2020) - Li, Jingchun; Liu, Yuanzhong; Li, Yiqiang; Yuan, Zhe; Xu, Hongwen; Canavese, Federico
Background: Percutaneous Achilles tenotomy (PAT) is an important component of the Ponseti method and is performed in 85% to 90% of patients. However, there is a lack of objective data assessing early radiographic changes in children undergoing PAT. Methods: Forty-nine patients with idiopathic clubfoot treated by Ponseti casting were prospectively enrolled between October 2017 and October 2018. Preoperative and postoperative ankle dorsiflexion (pre-ADF max, post-ADF max ) and lateral talocalcaneal angle (pre-LTCA max, post-LTCA max ) values with the ankle in maximal dorsiflexion as well as postoperative LTCA values with the ankle in the neutral position (post-LTCA neutral ) were measured. The relationship between the preoperative and postoperative ADF and LTCA values was studied using Pearson or Spearman correlation coefficients. Forty-nine patients (72 feet) were included; the mean age at initial treatment was 32.2 ± 24.1 days. Results: Post-LTCA max improved significantly from 18.6 ± 9.2 degrees to 25.1 ± 10.5 degrees ( P < .0001). Pre-ADF and pre-LTCA max showed a positive correlation in both the less than 28-day group ( r = 0.42; P = .015) and the Dimeglio III group ( r = 0.29; P = .035). However, post-ADF and post-LTCA max showed a positive correlation in the Dimeglio III group ( r = 0.30; P = .028). The degree of improvement in post-LCTA max in the Dimeglio III group was similar to that in the Dimeglio IV group ( P = .28). Conclusion: The LTCA increased immediately after PAT in clubfoot, although the improvement seemed to be unrelated to the severity of the disease. PAT led to an increase in both ADF and the LTCA, and it contributed to the improvements in subtalar joint motion and alignment. Level of Evidence: Level III, comparative study.